Drug repurposing as an alternative for the treatment of recalcitrant bacterial infections - Rangel-Vega, Adrian; Bernstein, Lawrence R.; Mandujano Tinoco, Edna-Ayerim; García-Contreras, Silvia-Julieta; García-Contreras, Rodolfo (Frontiers in Microbiology, 2015)
Bacterial infection remains one of the leading causes of death worldwide, and the options for treating such infections are decreasing, due the rise of antibiotic-resistant bacteria. The pharmaceutical industry has produced few new types of antibiotics in more than a decade. Researchers are taking several approaches toward developing new classes of antibiotics, including (1) focusing on new targets and processes, such as bacterial cell–cell communication that upregulates virulence; (2) designing inhibitors of bacterial resistance, such as blockers of multidrug eﬄux pumps; and (3) using alternative antimicrobials such as bacteriophages. In addition, the strategy of finding new uses for existing drugs is beginning to produce results: antibacterial properties have been discovered for existing anticancer, antifungal, anthelmintic, and anti-inflammatory drugs. In this review, we discuss the antimicrobial properties of gallium compounds, 5-fluorouracil, ciclopirox, diflunisal, and some other FDA-approved drugs and argue that their repurposing for the treatment of bacterial infections, including those that are multidrug resistant, is a feasible strategy.